Stress for Success: A Review of Timothy Geithner's Financial Crisis Memoir - Gorton, Gary (Journal of Economic Literature, 2015)
Timothy Geithner's memoir of the financial crisis of 2007–08—Stress Test: Reflections on Financial Crises—is an important historical document offering details of how policies were formed and implemented during the crisis, showing the political constraints, and offering lessons for future crises. Walter Bagehot's classic rule for fighting crises— that the central bank should lend against good collateral at a high rate—is passive and incomplete. Geithner argues for the use of overwhelming force to reestablish confidence. Also, although the Federal Reserve's new crisis lending programs needed to be anonymous so as not to reveal weak banks' identities—“stigma”—the stress tests during the crisis did reveal information that may have been useful in reestablishing confidence. (JEL B31, E44, E63, G01, G21, G28)